Pelatihan Menulis Cerpen yang Berkearifan Lokal Pada Siswa SMAN 2 Prabumulih - Hayatun Nufus; Juaidah Agustina; Masnunah; Mardiana Sari; Ratu Wardarita; Sitti Rukiyah; Yenny Puspita (PT FORMOSA CENDEKIA GLOBAL, 2022)
Cerpen or short stories are literary works in the form of prose. Short stories are works of high level imagination. The formulation of the problem in this service is